Educators' perceptions of HIV/AIDS in Mthatha. - Mpongwana, Zibongiwe (My University, 2014)
ABSTRACT This study undertook to explore the perceptions of educators in relation to HIV/AIDS in the workplace. Given that absenteeism can be disruptive of the fundamental teaching and learning activities in a school. There is a need for better information on the extent to which HIV/AIDS leads to poor teaching and learning. The data was collected in Mthatha by administering questionnaires to teachers, having interviews with managers of three schools and an Education Development Officer. The study revealed that there is inefficient bureaucratic procedures that result in the delays in granting sick leave and absenteeism management. Concomitantly the perceptions of policies, practises and attitudes that influence behaviour are not readily encouraging and reinforcing. The study recommends the need for revision of the already existing policy to develop a policy on sick leave entitlements and relief teachers which takes into account the HIV/AIDS situation. The research is informed by the realisation that parallel efforts to create supportive social environments, through building alliances between peer educators and more influential people is essential. Therefore, human capital is a determining factor for economic success, by investing in training and education there will be enhanced well being for individuals and communities as well as increased global advantage to fight the growing epidemic.
MM 2007
Keywords: AIDS (Disease),HIV infections.